2011
DOI: 10.1080/13611267.2011.543567
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a University‐Based Distance Education Mentoring Program from a Quality Management Perspective

Abstract: This study describes assessment results from the Distance Education Mentoring Program (DEMP) at Purdue University Calumet, Indiana, USA. The program, sponsored by the university's Vice Chancellor for Academic Affairs, was made available to all teaching faculty who wished to become protégés and develop their skills at teaching online courses. The DEMP is a university initiative designed to enhance the development of high-quality online courses by mentoring faculty in instructional design principles. Faculty mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Mentoring is an influential and interactive relationship whereby a subordinate is counselled, supervised, assisted and driven in the right direction by an expert and older academic on how to realise career development (Barczyk, 2011). Despite the extant literature highlighting that academics in universities are expected to benefit considerably when they are mentored, the findings of the research revealed otherwise because the majority of the participants had not been mentored.…”
Section: Discussionmentioning
confidence: 92%
“…Mentoring is an influential and interactive relationship whereby a subordinate is counselled, supervised, assisted and driven in the right direction by an expert and older academic on how to realise career development (Barczyk, 2011). Despite the extant literature highlighting that academics in universities are expected to benefit considerably when they are mentored, the findings of the research revealed otherwise because the majority of the participants had not been mentored.…”
Section: Discussionmentioning
confidence: 92%
“…According to Lankau and Scandura (2002), the mentee's learning process is made easier by the functions the mentor deploys. The positive role between the mentor's functions and the mentee's learning has been illustrated in other studies (Barczyk et al, 2011;Eby et al, 2004;Wanberg et al, 2003).…”
Section: Mentor's Functionsmentioning
confidence: 61%
“…As more courses at post-secondary institutions move toward an online or blended format (Munson et al, 2016), graduate students and new faculty need to be made aware of approaches to online and blended teaching and learning, and to develop the necessary competencies for teaching in those environments (Hixon et al, 2011;Lane, 2013). Sheffield et al (2015) proposed that the opportunity to understand the technology and dynamics of teaching in an online environment can be integrated into a graduate certificate program in university teaching and learning.…”
Section: Program Format: Online and Blended Programmingmentioning
confidence: 99%